Public administration in the era of digital and collaborative governance: a bibliometric analysis - Nasution, Mimin Sundari; Syahza, Almasdi; Rusli, Zaili; Mayarni, Mayarni; Mashur, Dadang; Zulkarnaini, Zulkarnaini; Ananda, Fajriani (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This research paper examines how digital governance evolves and intersects with collaborative governance to reshape the principles and practices of public administration. The research explores how digital platforms facilitate stakeholder collaboration, co-production of public services and evidence-based decision-making. The study also discusses the challenges that public institutions face in adapting to this new paradigm, including issues of digital divide, institutional resistance and governance capacity. These findings underscore the importance of aligning technological innovation with inclusive governance practices to achieve more effective, accountable and citizen-centred governance. The implications of this research suggest that future public sector reforms should prioritise digital inclusion, invest in collaborative capacity building, and strengthen governance networks to respond more adaptively to complex societal needs. Ultimately, this research suggests that the fusion of digital and collaborative governance offers significant potential to address complex policy challenges and enhance democratic legitimacy in contemporary public administration.